The Coexistence of Gravity Waves From Diverse Sources During a SOUTHTRAC Flight - Alexander, Peter; de la Torre, Alejandro; Llamedo, P.; Hierro, R.; Marcos, T.; Kaifler, Bernd; Kaifler, Natalie; Geldenhuys, Markus; Preusse, Peter; Giez, Andreas; Rapp, Markus; Hormaechea, J. L. (Journal of Geophysical Research: Atmospheres, 2023)
We use observations from one of the SOUTHTRAC (Southern Hemisphere Transport, Dynamics, and Chemistry) Campaign flights in Patagonia and the Antarctic Peninsula during September 2019 to analyze possible sources of gravity waves (GW) in this hotspot during austral late winter and early spring. Data from two of the instruments onboard the German High Altitude and Long Range Research Aircraft (HALO) are employed: the Airborne Lidar for Middle Atmosphere research (ALIMA) and the Basic HALO Measurement and Sensor System (BAHAMAS). The former provides vertical temperature profiles along the trajectory, while the latter gives the three components of velocity, pressure, and temperature at the flight position. GW-induced perturbations are obtained from these observations. We include numerical simulations from the Weather Research and Forecast (WRF) model to place a four-dimensional context for the GW observed during the flight and to present possible interpretations of the measurements, for example, the orientation or eventual propagation sense of the waves may not be inferred using only data obtained onboard. We first evaluate agreements and discrepancies between the model outcomes and the observations. This allowed us an assessment of the WRF performance in the generation, propagation, and eventual dissipation of diverse types of GW through the troposphere, stratosphere, and lower mesosphere. We then analyze the coexistence and interplay of mountain waves (MW) and non-orographic (NO) GW. The MW dominate above topographic areas and in the direction of the so-called GW belt, whereas the latter waves are mainly relevant above oceanic zones. WRF simulates NOGW as mainly upward propagating entities above the lower stratosphere. Model runs show that deep vertical propagation conditions are in general favorable during this flight but also that in the upper stratosphere and lower mesosphere and mainly above topography there is some potential for wave breaking. The numerical simulations evaluate the GW drag for the whole flight ...